MODIFIED CHITIN NANOFIBER/ CELLULOSE ACETATE BASED MEMBRANE AS LI-ION BATTERY SEPARATOR - Putih Puspa Asri, Putri
The growth of Li-ion battery consumption in particular has increased significantly to support emission reduction plans, the development of renewable energy systems, and to minimize the impact of pollution that causes environmental damage. However, the growing demand for Li-ion batteries in the future will also be proportional to the increase of battery waste. Battery waste can be recycled to obtain active material from the electrodes, though the components such as separator cannot be recycled and are not easily degraded. The commercial separator composed of polyolefin material which is not biodegradable and not sustainable. To support the prevention of environmental damage, in this research, an alternative separator was made from biopolymer chitin nanofiber (CH) with a mixture of cellulose acetate (CA). The modified CA/CH separator was fabricate using the phase inversion technique. The obtained membrane has a thickness between 100-180 m. The results of Scanning Electron Microscopy characterization showed an asymmetric pore structure with various pore size. The mixture of chitin nanofibers in cellulose acetate can prevent the formation of wrinkles in the membrane fabrication process. Thermal analysis using Thermogravimetry Analysis showed an increase in thermal stability in the presence of chitin nanofiber (CH). The thermal shrinkage test showed that the membrane was dimensionally stable with a shrinkage rate of 4% at a temperature of 90oC compared to commercial PP separator (Celgard 2400). Membrane with 15 % (w/v) CH concentration showed high electrolyte absorption around 800%, 65% porosity and conductivity value of 5.7 x 10-1 mS.cm-1. This high conductivity value are expected to support optimal battery performance.